Gambaran Pengetahuan, Sikap, dan Perilaku Mahasiswa Kedokteran Universitas Tarumanagara terhadap Pemberian Insulin pada Diabetes Melitus Tipe 2 - Medinahtul Rahman; Hari Sutanto (Jurnal Siti Rufaidah, 2026)
Type 2 diabetes mellitus is a chronic metabolic disease that requires comprehensive management, including insulin therapy; therefore, the knowledge, attitudes, and practices of medical students as future physicians play an important role in therapeutic success. This study aimed to describe the level of knowledge, attitudes, and practices of medical students of the Faculty of Medicine, Universitas Tarumanagara, Class of 2022, regarding insulin administration in patients with type 2 diabetes mellitus. This study employed a quantitative descriptive design with a cross-sectional approach involving 93 respondents. Data were collected using questionnaires assessing knowledge, attitudes, and practices related to insulin administration and analyzed descriptively. The respondents had a mean age of 21.08 years (median 21; range 20–26 years) and were predominantly female (69 respondents; 75.5%). The results showed a mean knowledge score of 8.5 ± 1.47, with 56.1% of respondents categorized as having good knowledge. Attitudes toward insulin administration had a mean score of 7.67 ± 1.25, with 56.1% classified as good, while insulin administration practices were categorized as very good, with a mean score of 9.99 ± 0.74 and 95.7% of respondents in the good category. This study indicates that medical students of Universitas Tarumanagara Class of 2022 possess good levels of knowledge, attitudes, and practices regarding insulin administration in patients with type 2 diabetes mellitus.